Financial Statement Fraud in Sharia-Compliant Companies: The Predictive Relevance of Fraud Hexagon Theory - Wahyuni, Nella; Afandi, Ahmad; Maarif, Muhammad Ariful (Kunuz: Journal of Islamic Banking and Finance, 2025)
This study examines the influence of factors within the Fraud Hexagon theoretical framework on the occurrence of financial statement fraud among companies listed on the Jakarta Islamic Index (JII). The study applies the fraud hexagon model, where financial targets and financial stability proxy the stimulus factor; nature of industry and ineffective monitoring represent opportunity; auditor changes reflect rationalization; changes in the board of directors capture capability; CEO education level represents ego; and political connections proxy collusion. Financial statement fraud is detected using the Beneish M-Score Model. The research population comprises all firms listed on JII during the 2020–2024 period, with a final sample of 26 companies and 130 firm-year observations selected through purposive sampling. Logistic regression analysis is employed using SPSS version 29. The results indicate that financial stability has a positive and significant effect on financial statement fraud, while financial targets and nature of industry exhibit negative and significant effects. In contrast, ineffective monitoring, auditor changes, changes in directors, CEO education level, and political connections do not show a significant influence on financial statement fraud.